2021
DOI: 10.3389/fendo.2021.708248
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Estrogen Receptor Alpha and Beta on Endogenous Ligands of Peroxisome Proliferator-Activated Receptor Gamma in Papillary Thyroid Cancer

Abstract: PurposeThe inhibition of estrogen receptor alpha (ERα) or the activation of ERβ can inhibit papillary thyroid cancer (PTC), but the precise mechanism is not known. We aimed to explore the role of ERα and ERβ on the production of endogenous peroxisome proliferator-activated receptor gamma (PPARγ) ligands in PTC.Methods2 PTC cell lines, 32 pairs of PTC tissues and matched normal thyroid tissues were used in this study. The levels of endogenous PPARγ ligands 15(S)-hydroxyeicosatetraenoic acid (15(S)-HETE), 13-S-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Prior research has reported that suppression of ERα or activation of ERβ can inhibit TC development by inducing the apoptosis of TC cells 24 . The Ki‐67 proliferation index reflects the malignant behavior of TC 25 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has reported that suppression of ERα or activation of ERβ can inhibit TC development by inducing the apoptosis of TC cells 24 . The Ki‐67 proliferation index reflects the malignant behavior of TC 25 .…”
Section: Resultsmentioning
confidence: 99%
“…ERα and ERβ are involved in the progression of TC, playing opposite roles in the growth of TC cells, 24 and upregulation of ERα/ERβ protein ratio facilitates the papillary TC development 39 . Low ERβ expression is associated with poor survival in follicular TC, 40 and its expression is lower in papillary TC tumor tissues than in adjacent normal thyroid tissues 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crosstalk between PPARG and ER suppresses the proliferation and migration of thyroid cancer cells [ 106 ]. In contrast, stimulation of PPARγ signaling leads to ER inhibition and induces apoptosis in papillary thyroid cancer cells [ 107 ]. Overexpression of HER2 induces upregulation of PPARG transcription and translation in ER+ MCF-7 cells [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…ERa induced prosurvival autophagy through generating the reactive oxygen species and activating ERK1/2 in thyroid cancer (14). In addition, we also reported that the differential role of ERa and ERb in thyroid cancer mediated the production of endogenous PPAR-g ligand (15). Upregulated ERa/ ERb ratio by PES1 will promote the occurrence and development of papillary thyroid cancer (PTC) (16).…”
Section: Introductionmentioning
confidence: 93%